Desenvolvimento de um Receptor ISDB-T 1-Seg através de Rádio Definido por Software - Muttoni, Leonardo (2017)
This work presents the development of a one-segment (1-seg) digital TV receiver for the Integrated Services Digital Broadcasting - Terrestrial (ISDB-T) standard, based on Software Defined Radio (SDR). The proposed receiver works in real time and requires a computer and the RTL-SDR, a low-cost SDR hardware platform. Signal processing performed in software provides an important framework for the study of the ISDB-T standard in practice. The results of the receiver operation, the performance of its main radio functions and the workload imposed on the CPU are presented.